SYNTHESIS OF A LEVER-CAM MOTION TRANSDUCER FOR A ROTARY VANE PUMP (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article solves problem of synthesizing a lever-cam motion transducer that converts rotary motion of input shaft of a rotary pump into motion of its vanes required for volumetric pumping of gases and liquids. Analytical expressions for theoretical profile of cam of lever-cam transducer of the movement of rotary vane pump are obtained. The cam profile was built according to analytical expressions.